Effects of green manure and poultry manure on strawberry production and soil fertility - Hülya Sayğı (International Journal of Recycling of Organic Waste in Agriculture)
Purpose In this study, the effects of green manure and animal waste on economic of strawberry yield, fruit quality and soil fertility were investigated.Method The experiment was set up with four replicates in a randomized complete block design. The treatments consisted of green manure parcels divided into two parts and green manure + poultry manure slurry were given to one part, and the other part was not applied complete. Seed planting was carried out in the first year of the experiment (2015) while strawberry plants were removed during the second year (2016) and the seeds of green manure plants were planted. Soja hispida [Soja] and Vigna sinensis [Cowpea] plants were mown and mixed into the soil when they were in bloom.Results The results from the study shows that the yield realized from control plot during first year was between 10.68 and  22.33 t ha-1, second year yield was between 8.81  and 23.39 t ha-1 and  third year was 10.68 and 16.98 t ha-1. After harvest, soil organic matter content increased by 12% in the first year and 5.10% in the second year in green manure + poultry manure slurry application, the total nitrogen content increased by 75% in the first year and 10% in the second year. In the fruit, it gave higher content of Vitamin C and nitrate level.Conclusion From our findings, it was discovered that green manure and poultry manure slurry gave better results in terms of fruit yield, quality, soil fertility and economy.